Pemberdayaan UMKM Dapur Pak Gendut melalui Media Sosial - Mayang Viona Afifa; Rizki Oktaviani; Alvina Nathaniela Andini (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The digital era presents various challenges for the culinary MSME "Dapur Pak Gendut," including the use of traditional marketing methods, limited promotional reach, inconsistent content posting, and suboptimal use of social media as a digital marketing tool. The objective of this empowerment activity is to increase the effectiveness of digital marketing by optimizing the use of social media platforms such as TikTok, Instagram, and WhatsApp Business. The method used is a participatory approach through observation, outreach, education, mentoring, and activity evaluation. The implemented solutions include creating social media accounts, training in creating visual product content, writing communicative promotional copywriting, scheduling regular content uploads, and optimizing consumer interactions. Furthermore, this activity contributes to increasing digital business literacy, allowing marketing to be managed in a more modern and effective manner. The results of the activity indicate that utilizing social media as a digital marketing tool has successfully increased marketing reach beyond the region, increased the number of customers from an average of 15–25 to 45–60 per month, increased the frequency of promotions to 3–4 times per week, and driven a 2–3-fold increase in product sales compared to before the program was implemented.